Management of abdominal pain: clinical guidelines of the Russian gastroenterological association - V. T. Ivashkin; I. V. Mayev; Yu. A. Kucheryavy; T. L. Lapina; Ye. K. Baranskaya; M. F. Osipenko; M. A. Livzan; V. B. Grinevich; Ye. I. Sas; O. M. Drapkina; A. A. Sheptulin; D. I. Abdulganiyeva; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.